2016
DOI: 10.1016/j.neulet.2016.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Examining cortical thickness in male and female DWI offenders

Abstract: Some sex differences have been detected in driving while impaired by alcohol (DWI) offenders. However, understanding of the key factors contributing to DWI among male and female drivers remains elusive, limiting development of targeted interventions. Sex-based neurocognitive analyses could provide the much-needed insight. We examined whether male DWI offenders show cortical thickness anomalies that differ from those in female DWI offenders, when compared to their respective controls. Moderating role of sex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…(Brown, Ouimet, Nadeau, Tremblay, & Pruessner, 2015). In subsequent analyses, however, we detected structural anomalies in the posterior cingulate cortex (Dedovic et al, 2016), but only when alcohol misuse was relatively low and at levels comparable to that seen in the younger DWI drivers here. The posterior cingulate cortex is a complex brain structure that has been associated with the signaling of environmental change and the need to alter behaviour (Leech, Braga, & Sharp, 2012).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…(Brown, Ouimet, Nadeau, Tremblay, & Pruessner, 2015). In subsequent analyses, however, we detected structural anomalies in the posterior cingulate cortex (Dedovic et al, 2016), but only when alcohol misuse was relatively low and at levels comparable to that seen in the younger DWI drivers here. The posterior cingulate cortex is a complex brain structure that has been associated with the signaling of environmental change and the need to alter behaviour (Leech, Braga, & Sharp, 2012).…”
Section: Discussionmentioning
confidence: 47%
“…This frontal system assists in goal-directed behaviour and inhibition, and typically reaches full development by the mid to late 20's (Casey, Jones, & Hare, 2008). Disruptions in frontal-limbic systems are associated with excessive risk taking in adolescents and young adults (Dahl, 2008;Gianotti et al, 2009;Mäntylä, Karlsson, & Marklund, 2009;Steinberg & Laurence, 2010), compulsive behaviours and substance abuse in adults (Bechara, Dolan, & Hindes, 2002b;Dom, Sabbe, Hulstijn, & van den Brink, 2005;Koob, 2009;Potenza, Sofuoglu, Carroll, & Rounsaville, 2011;Verdejo-Garcia & Bechara, 2009), reckless driving (Ba, Zhang, Peng, Salvendy, & Crundall, 2016;Brown et al, 2016;Cheng, Ng, & Lee, 2012;Farah, Yechiam, Bekhor, Toledo, & Polus, 2008;Foy et al, 2016;Lev, Hershkovitz, & Yechiam, 2008;O'Brien & Gormley, 2013;Ross et al, 2015;Tabibi, Borzabadi, Stavrinos, & Mashhadi, 2015), and impaired driving (Bouchard, Brown, & Nadeau, 2012;Dedovic et al, 2016;Kasar, Gleichgerrcht, Keskinkilic, Tabo, & Manes, 2010;Ouimet et al, 2007). Overall, evolution across the lifespan in these systems represents a crucial backdrop for understanding individual differences in crash risk.…”
Section: Introductionmentioning
confidence: 99%
“…The structure and activation of the PCC have been related to the decision-making process in delay discounting tasks [ 51 , 59 , 134 , 135 ]. Furthermore, Dedovic et al [ 18 ] have found a reduced cortical thickness in this area in men who had driven under the influence of alcohol. Regarding the occipital cortex, structure and functional connectivity data have related this area to delay discounting rates [ 61 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sakai et al [ 17 ] found that older people with lower executive function had a lower volume in the supplementary motor area (SMA) and, more importantly, were prone to risky driving. Dedovic et al [ 18 ] found that men who had driven under the influence of alcohol (without engaging in other dangerous drinking patterns) showed a reduced cortical thickness of the posterior cingulate cortex (PCC) compared with drivers in the control group. Finally, Aydogan et al [ 19 ] observed that drivers who reported driving faster than the allowable speed limit had lower GMV in the ventromedial and dorsolateral prefrontal cortices, amygdala, and striatum.…”
Section: Introductionmentioning
confidence: 99%